2020
DOI: 10.1111/jan.14459
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of an instrument of occupational low back pain prevention behaviours of nurse

Abstract: Aim: To develop and test the psychometric properties of occupational low back pain prevention behaviours questionnaire in nursing personnel. Design: A qualitative and quantitative research design to develop and validate an instrument. Methods: A qualitative study was conducted from May-October 2017 with 20 participants to generate an item pool. Then, content and face validity was carried out. Next, the questionnaire was distributed among a sample of nurses. In all, 150 nurses participated (mean age 34.1; SD 7.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…The Cronbach's α coefficient can reflect the homogeneity of items in questionnaire ( 34 ). The results showed that the Cronbach's α coefficient of the Chinese version of the questionnaire was 0.885, and the Cronbach's α coefficient of each dimension ranged from 0.903 to 0.924, which is slightly higher than the result of the original questionnaire ( 24 ), indicating that the items of the Chinese version of the questionnaire has higher internal consistency. Similarly, the split-half reliability coefficient was 0.663, which once again confirms the above conclusion.…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…The Cronbach's α coefficient can reflect the homogeneity of items in questionnaire ( 34 ). The results showed that the Cronbach's α coefficient of the Chinese version of the questionnaire was 0.885, and the Cronbach's α coefficient of each dimension ranged from 0.903 to 0.924, which is slightly higher than the result of the original questionnaire ( 24 ), indicating that the items of the Chinese version of the questionnaire has higher internal consistency. Similarly, the split-half reliability coefficient was 0.663, which once again confirms the above conclusion.…”
Section: Discussionmentioning
confidence: 76%
“…The results showed that I-CVI ranged from 0.857 to 1.000, and Q-CVI was 0.952, which is higher than the reference value of content validity of 0.9 and 0.8, respectively ( 36 ). Furthermore, the EFA results showed that the six common factors of the Chinese version of the questionnaire explained 73.623% of the total variance, and the factor loading of each item in the questionnaire was >0.4, and the factor attribution of each item was consistent with the original version ( 24 ), which indicating that the Chinese version of the questionnaire has suitable construct validity. Meanwhile, in CFA, the fitting index of the Chinese version of the questionnaire was within the acceptable range and stronger than that of the original version ( 24 ).…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations